Bacterio-opsin mRNA in wild-type and bacterio-opsin-deficient Halobacterium halobium strains - DasSarma, Shiladitya (1984)
We have examined transcripts corresponding to the Halobacterium halobium bacterio-opsin (BO) gene in wild-type and in BO-deficient mutant strains containing the insertion elements ISH1 or ISH2 in the BO gene. BO mRNA from the wild-type strain was purified by hybrid selection using single-stranded cDNA. Labeling by vaccinia virus capping enzyme and [α-(32)P]GTP showed that it contains the 5′-terminal nucleotide of the primary transcript. Sequence analysis showed that transcription begins only two nucleotides upstream of the initiator codon for BO. Two species of BO mRNA were found; the major species has a ragged 3′ terminus ≈45 nucleotides downstream from the terminator codon for BO, while the minor species is about 170 nucleotides longer at the 3′ end. Analysis of the transcripts in several BO gene mutant strains by RNA gel-transfer hybridization showed that (i) mutants with ISH1 insertions within the NH(2)-terminal coding region of the gene contain no detectable transcripts, (ii) mutants with ISH2 near the middle of the coding region of the gene contain multiple incomplete transcripts, and (iii) a mutant that is partially BO deficient due to an insertion of ISH2 100 base pairs upstream of the site of initiation of transcription contains a decreased level of BO mRNA.